Characteristic of elite male 800-m runner`s race performance based on hybrid computing methods - Chen, C.; Ma, J.; Song, J.; He, S.; Tan, M. (Applied Bionics and Biomechanics, 2023)
The purpose of the study was to analyze the characteristics of elite men`s 800-m race performance, which help coaches to obtained the winning experience of 800-m race and prepare for athletes` training more efficiently. Hybrid computing methods were applied to analyze athletes` race performance. The study found that the competitive capability of elite athletes mainly include maximal speed running, speed endurance, and even pacing running. The maximal speed advance from 700-800 to 100-200-m sector, the velocity is also increase at the same time. The first peak speed (100-200 m) is higher than the second (500-600 m). Reduce the 0-400 m split times could be contributing to achieve personal best. 200-400 m is the even pacing phase which have the function of adjust physiological condition and preserve energy. The speed endurance was the most important factor to won the 800-m race. Place in permanent ranking and adopt the follow-running tactic can increase the odds to be medalist.